2011
DOI: 10.1371/journal.pone.0024753
|View full text |Cite
|
Sign up to set email alerts
|

MMP Mediated Degradation of Type VI Collagen Is Highly Associated with Liver Fibrosis – Identification and Validation of a Novel Biochemical Marker Assay

Abstract: Background and AimsDuring fibrogenesis, in which excessive remodeling of the extracellular matrix occurs, both the quantity of type VI collagen and levels of matrix metalloproteinases, including MMP-2 and MMP-9, increase significantly. Proteolytic degradation of type VI collagen into small fragments, so-called neo-epitopes, may be specific biochemical marker of liver fibrosis. The aim of this study was to develop an ELISA detecting a fragment of type VI collagen generated by MMP-2 and MMP-9, and evaluate this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
138
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(141 citation statements)
references
References 34 publications
(54 reference statements)
3
138
0
Order By: Relevance
“…In support of a role for type VI collagen in NASH-related fibrosis, studies have demonstrated its prominent expression in areas of active scar formation [35,36], and elevated serum levels of the collagen VI core structure (which lacks the endotrophin domain) have been shown to be associated with advanced liver fibrosis in rodents [37], humans [38][39][40][41], and with elevated portal pressure [42]. The expression of procollagen α3(VI) is regulated by PPARγ and our findings are in alignment with this.…”
Section: Discussionmentioning
confidence: 98%
“…In support of a role for type VI collagen in NASH-related fibrosis, studies have demonstrated its prominent expression in areas of active scar formation [35,36], and elevated serum levels of the collagen VI core structure (which lacks the endotrophin domain) have been shown to be associated with advanced liver fibrosis in rodents [37], humans [38][39][40][41], and with elevated portal pressure [42]. The expression of procollagen α3(VI) is regulated by PPARγ and our findings are in alignment with this.…”
Section: Discussionmentioning
confidence: 98%
“…Promising candidates have been reported, including those derived from type IV collagen, 196,197 type I collagen, 198 type V collagen, 199 and type VI collagen. 200 Systemic approaches, such as global profiling of serum glycoproteins, have also been utilized, 201 and this technique is now being validated in rodent models (e.g., Fang et al, 202 Blomme et al,…”
Section: -178mentioning
confidence: 99%
“…A range of serological assessments have been developed to investigate some of the key structural proteins of the ECM (Table 3). 56,60,129,144,[196][197][198][199][200]217,274,276,278,311,314,[331][332][333][334][335][336][337][338][339][340][341][342][343][344][345][346][347] Measurement of these proteins may provide key information in clinical settings on the tissue turnover profile, and thereby assists in patient diagnosis, in identification of those patients in most need of treatment, and finally, in monitoring of clinical efficacy of interventions. These technologies may also be used in preclinical settings, in ex vivo and in vitro cultures, to determine the molecular mode of action in the assembly and maintenance of the matrix.…”
Section: 311mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, MMPs are promptly expressed by activated HSCs in response to diverse hepatic injury and are considered to promote disease progression. 38 Thus, MMPs play a dual role in liver fibrosis, depending on the timing of their production. The early temporary high expression of MMPs may destroy the surrounding tissue in order to deposit newly synthesized ECM.…”
Section: ■ Discussionmentioning
confidence: 99%